(untitled) (Baghdad Science Journal, 2016)
The present study was designed in the aquaculture and fish nutrition research aquarium in the College of Veterinary Medicine/Baghdad University from a period 1/3 to 1/6/2013 to investigate the toxicity of the herbicide glyphosate aqua on Barbus sharpeyi fish. Fish fingerlings were used with average weight between 10 – 15 gm to measure the (LC50), and 200 fingerlings were used to know the acute and chronic toxic effect for the herbicide. The fingerlings were randomly distributed as 10 fish for each aquarium. Fish were divided into four treatments and control group (without addition of herbicide). The first processing with a concentration of 0.415 mg/L for a duration of exposure 90 days, the second processing group with a concentration 0.415 mg/L for 15 days, while the third group was treated with 0.207 mg/L of the herbicide for a duration of exposure, the forth group was exposed to 0.207 mg/L for 15 days only. The study aimed to determine the extent of the effect of the pesticide in the activity of liver enzymes, which included Alkaline phosphatase (ALP), Aspartate amino transfers (AST) and Alanine amino transfers (ALT). The results of biochemical tests for liver enzymes to fish experience has shown a rise in activity of enzymes which increased with duration of exposure. The first and the third treatments has a significant differences (P ?0.05) compared with control group. Results of the experiment to improvement in the health status of fish in second and forth treatments compared to control group.